EKSTRAKSI MINYAK NABATI SECARA FERMENTASI - Soeka, Yati Sudaryati (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Method of extracting vegetable oil from peanut and soybean cream through enzymatic fermentation was studied. Creams were incubated with respective strains of Bacillus sublilis, Candida rugosa and Pseudomonas aerogenes separately under mild condition that allowed for production of oil at pH 4.5-6.5 and room temperature overnight. A considerably amount of oil could be extracted from media containing coconut and peanut cream, however, none from soybean cream.The oil recovery was about 10 to 30% from approximately 46 to 52% total fat contained in the respective substrates.Those oil were extracted by application of culture filtrate of B. subtilis and C. rugosa exhibited higher linoleic and Iinolenic acid (0.50 to 0.61 % and 0.31 to 0.32% respectively), compared to those were of P. aerogenes lipase (0.20% and 0.13%, respectively).Further investigation was aimed to study the capacity of microbial strains on enzymatic reaction of fatty acid to fatty acid ester by incubating extracted oil in the present of organic solvents.